Pengaruh Dimensi Ujung Pemukul Terhadap Penggilingan Kulit Kerang Dengan Mesin Hammer Mill - Mohammad Nasih; Ikhwanul Qiram; Anas Mukhtar (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2021)
Hammer mill is a machine for crushing hard materials and flour. By modifying the hammer shapes and varying the motor rotation speed, it is hoped that it will be able to crush the shells into powder with different product dimensions. The quality of the product produced will describe the performance of the hammer mill machine. Experiments were carried out by making the ends of the batter dimensions 1, 2 and 3 cm with a motor speed of 1000 rpm, 1100 rpm and 1200 rpm. The highest yield of the 3 cm bat type is at 1200 rpm at 96.7%. Keywords: Clamshell, Hammer Mill